Aplikasi Geolistrik Resistivitas Konfigurasi Wenner-Schlumberger untuk Pemetaan Sebaran Leachate di Sekitar TPA Putri Cempo Surakarta: Chiranjeevi Nugroho, Darsono, Ari Handono Ramelan - Chiranjeevi Nugroho Chiranjeevi Nugroho; Darsono Darsono; Ari Handono Ramelan Ari Handono Ramelan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Mapping leachates distribution using geoelectrical resistivity has been done at Plesungan village, Gondang Rejo, Karanganyar regency. Acquisition using Wenner-Schlumberger configuration with space of the smallest electrode is 15 meters away. This research uses resistivitymeter OYOMcOHM-EL for current injection and measure the potential difference. Inversion process uses Res2dInv software for 2 dimensions model and RockWorks16 software for 3 dimensions model. The location of the research has geology old alluvium with characteristics conglomerate, sandstone, silt and clay. Leachate mapping estimates resistivity value of <5.55 Om with the direction away from the final disposal site where the main constituent of reseach sites is clay.